2014
DOI: 10.3163/1536-5050.102.4.009
|View full text |Cite
|
Sign up to set email alerts
|

Current status of information literacy instruction practices in medical libraries of Pakistan

Abstract: Medical librarians need to develop educational partnerships with faculty for integrating IL instruction into the mainstream curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…Most of the students enrolled in the health sciences schools in Pakistan hardly have any library experience, due to the absence of information services at higher secondary level. Moreover, health sciences librarians offer a preliminary level of IL instruction to students in health sciences schools in Pakistan (Ameen & Ullah, 2016;Ullah & Ameen, 2014a, 2014b; therefore, the IL skills of students could not be developed to the satisfactory level. Baro et al (2011) also reported the lack of IL skills among health sciences students in Nigeria, another developing country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the students enrolled in the health sciences schools in Pakistan hardly have any library experience, due to the absence of information services at higher secondary level. Moreover, health sciences librarians offer a preliminary level of IL instruction to students in health sciences schools in Pakistan (Ameen & Ullah, 2016;Ullah & Ameen, 2014a, 2014b; therefore, the IL skills of students could not be developed to the satisfactory level. Baro et al (2011) also reported the lack of IL skills among health sciences students in Nigeria, another developing country.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is the second part of a two phase, sequential mixed method study, aimed to identify strategies for the effective implementation of IL instruction for medical students, studying medicine at undergraduate and postgraduate level in medical schools and universities of Pakistan. The quantitative (first phase) findings were presented at the European Conference on Information Literacy held in 2014, and the paper has been published in the conference proceedings (Ullah & Ameen, 2014a, 2014b). The questionnaire survey (first phase) has revealed that health sciences librarians in Pakistan rated the IL skills of their medical students as inadequate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They identified seven key competencies, relating to user education, where most working librarians require training. A recent national study of information literacy (IL) instruction practices in medical libraries revealed that IL instruction was mostly provided to new students and first time users as and when requested . Only a small number of institutions claimed to have integrated IL instruction into the curriculum without the collaboration of their medical faculty.…”
Section: Health Sciences Information Services In Pakistan In the 21stmentioning
confidence: 99%
“…A recent national study of information literacy (IL) instruction practices in medical libraries revealed that IL instruction was mostly provided to new students and first time users as and when requested. 4 Only a small number of institutions claimed to have integrated IL instruction into the curriculum without the collaboration of their medical faculty. Face to face instruction, group-or individual-based, conducted at the reference desk, computer lab or lecture hall were the most common delivery methods.…”
Section: Introduction Of Information Literacy Instructionmentioning
confidence: 99%